Digital Holographic Positioning Sensor for a Small Deployable Space Telescope - Eduard R. Muslimov; Airat Zh. Sakhabutdinov; Oleg G. Morozov; Nadezhda K. Pavlycheva; Damir M. Akhmetov; Danila Yu. Kharitonov (Applied Sciences, 2022)
We propose a system and a technique to measure misalignments of individual optical elements in a deployable telescope for a small satellite, and we demonstrate its application for a 2230 mm F10.3 Ritchey–Chretien type telescope. The system uses laser point sources at the edge of each of the deploying segments to form an interference pattern at the telescope image sensor. By processing the interferograms in the Fourier domain and comparing them to the computed ones, it becomes possible to measure the position of the primary mirror segments with a precision of <semantics>0.8<mspace width="3.33333pt"></mspace>μ</semantics>m and the axial displacement of the secondary mirror with the precision of <semantics>0.1</semantics> nm. Such a system would allow to build a deployable telescope fitting in a 1U CubeSat and align it in space with a sufficient accuracy, thus providing a gain in collecting power, reaching a factor of 2.49 with respect to a single mirror telescope fitting on a 1U CubeSat.